Bedside Ultrasonography in Evaluating Mediastinum Leakage in an Extremely-Low-Birth-Weight Infant with Esophageal Perforation - Mitsuhiro Haga; Yumiko Sato; Tomo Kakihara; Wakako Sumiya; Masayuki Kanno; Tetsuya Ishimaru; Masaki Shimizu; Hiroshi Kawashima (Thieme Medical Publishers, Inc., 2022)
Esophageal perforation in premature infants is a life-threatening condition that requires prompt treatment. Contrast-enhanced computed tomography (CECT) is recommended for diagnosis. However, it is difficult to obtain CECT images in premature infants because of their unstable conditions. We encountered a case of esophageal perforation in an extremely-low-birth-weight female infant. Bedside ultrasonography was useful in the diagnosis and follow-up evaluation of leakage in the mediastinum. Ultrasonography can be a useful modality for the evaluation of perforation of the lower part of the esophagus in premature infants.